Correlations between gluten aggregation properties defined by the GlutoPeak test and content of quality-related protein fractions of winter wheat flour. (November 2015) - Marti, Alessandra; Augst, Elliot; Cox, Steven; Koehler, Peter
Abstract: The gluten aggregation properties of 19 winter wheat cultivars were investigated using a rapid small-scale (7 min, 8.5 g flour) technique (GlutoPeak test, GPT). Correlations between GPT indices and gliadin (GLIA), glutenin (GLUT), SDS-soluble protein (SDSS), and glutenin macropolymer (GMP) concentrations were established. Two groups of samples were distinguished based on the shape of their GPT curves. Flours of group 1 gave curves with a slower buildup in torque (measured as aggregation time) and a higher area under the curve at peak (maximum torque), compared to those of group 2. Group 1 was characterized by lower GLIA and higher GLUT and GMP contents than group 2. GLIA (r = 0.70, p ≤ 0.001) and SDSS (r = 0.59, p ≤ 0.01) concentrations were significantly correlated to peak torque. GLUT and GMP contents were correlated to the aggregation time (GLUT: r = 0.72, p ≤ 0.001; GMP: r = 0.77, p ≤ 0.001) and the area under the curve at peak (GLU: r = 0.68, p ≤ 0.01; GMP: r = 0.78, p ≤ 0.001), confirming the importance of GMP for gluten strength. GPT could be an alternative to the labor-intensive quantitation of quality related protein fractions of wheat flour. Highlights: Wheat quality evaluation by fast and reliable tests is still a challenge. GlutoPeak test (GPT) is a rapid small-scale technique that measures gluten aggregation. Correlations between GPT indices and gluten proteins composition are established. GPT is an alternative to the labor-intensive quantitation of protein fractions.